The introduction of a 'monthly living wage' in Slovenia. (August 2019) - Poje, Andreja
This article provides a chronological account of the Slovenian trade unions' successful campaign to turn the statutory national monthly minimum wage into a living wage. The campaign led to a 23 per cent increase in the minimum wage and a change of its adjustment mechanism in 2010 and successive changes to its definition. The analysis starts with a historical overview of minimum wage developments in Slovenia and an account of the events prompting trade unions to launch their campaign. Reviewing the impact of the 23 per cent minimum wage increase, the Slovenian experience shows that turning the monthly minimum wage into a living wage does not necessarily lead to negative macroeconomic effects in terms of reduced growth or increased unemployment. The example of Slovenia furthermore illustrates that, even though the campaign was not explicitly couched in terms of a living wage campaign, the trade unions managed to adapt key elements of the living wage concept to the country-specific institutional context.